Power your tribe : create resilient teams in turbulent times - Comaford-Lynch, Christine (McGraw Hill-Ascent Audio, 2018)
WALL STREET JOURNAL AND USA TODAY BESTSELLER Is your team thriving in a world of relentless and rapid change? From the New York Times bestselling author of SmartTribes and Rules for Renegades comes a potent set of neuroscience-based tools to empower your team in uncertain times. Whether it's diminished sales, increased competition, or corporate restructuring, change is a natural part of doing business in today's high-speed, information-overload, instant-response environment. But inherent in human nature is resistance to change-a basic emotional response that is well-documented by neuroscience. In this groundbreaking guide, top leadership consultant and employee engagement expert Christine Comaford shows you how to bring your tribe together to tackle any challenge head-on. Using her simple, proven strategies, you'll be able to: * Meet the demands of changing markets, customers, and competitors * Adapt to new management, restructuring, and other corporate shakeups * Spark innovation and teamwork in the workplace-and keep it burning * Empower your people to embrace change as a new opportunity for growth Filled with case studies and all-too-familiar examples, this book will enable you to release resistance to change, build more emotionally agile teams, and mobilize the entire organization quickly and efficiently toward a clear and common goal. By training and empowering your team members to shift their emotional states-and see the positive potential of change-you can lead your tribe through any challenge and ensure success for years to come.